Wyznaczniki efektywności w strukturach teorii nauczania-uczenia się literatury = Determinants for Efficiency in the Structure of the Theory of Teaching and Learning Literature - Biłos, Edward (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The theme of this article is the efficiency problem in the structure of the theory of teaching and learning literature. This efficiency depends among other on such attributes, planned in the theories of literary didactics and defined by efficiency determinants - thanks to which in the case of adoption of these theories socially worthful ends beyond the limits of perception are carried into effect to the highest degree - as subjectivity, essence, systematization and historicity, which the author handles by means of three suitably selected different theories of teaching literature: the theory of "literary partition in school" by Mr. K. Wóycicki, the theory of literary communication in school and the theory of systematic perception of a piece of literary work by Mr. W. Pasterniak.
Keywords: dydaktyka literatury; nauczanie; efektywność